The effect of silver nitrate and silver thiosulphate on in vitro shoot regeneration of australian pink finger lime (Citrus australasica cv. Mia Rose) - Qiao, Stephanie Er Wong; Sreeramanan Subramaniam,; Bee, Lynn Chew (Penerbit Universiti Kebangsaan Malaysia, 2024)
Citrus australasica, commonly known as the finger lime, is a distinctive fruit indigenous to the coastal rainforest of Australia. It is renowned for its unique appearance, tangy flavor, and multiple medicinal properties. Additionally, its unique caviar-like pulp has garnered significant attention in the culinary industry. Conventional propagation of C. australasica is challenged by incompatibility issues during grafting and budding, its monoembryonic nature, and the lengthy time required to flower and bear fruits. Micropropagation on the other hand is an efficient alternative to conventional propagation for various commercial crops including citruses. However, the issue of leaf abscission was previously observed in C. australasica cultures, which has resulted in reduced shoot viability. The current study aimed to determine the effects of silver nitrate (AgNO3) and silver thiosulphate (STS) on in vitro shoot regeneration of C. australasica cv. Mia Rose. Nodal explants were cultured on half-strength Murashige and Skoog (MS) media supplemented with AgNO3 at 2.00, 4.00, 6.00, 8.00, and 10.00 mg/L and STS at 10.00, 20.00, 40.00, 60.00 and 80.00 μM in combination with 2.00 mg/L 6-benzylaminopurine (BAP). Results demonstrated that 4.00 mg/L AgNO3 resulted in the highest shoot number and length (2.65 ± 0.18 and 0.27 ± 0.03 cm respectively), while treatment with 10.00 μM STS resulted in the highest number of shoots and shoot length (2.36 ±0.19 and 0.32 ± 0.04 cm respectively). No leaf abscission was observed for all treatments of AgNO3 and STS after eight weeks of culture. This study underscored the efficacy of AgNO3 and STS as potent ethylene antagonists in shoot cultures of C. australasica cv. Mia Rose, suggesting their potential utilization in the micropropagation of the finger lime species.